Academic perspectives on teaching international family law in higher education institutions in England and Wales. Issue 1 (2nd January 2020) - Speed, Ana
ABSTRACT: The increasing prevalence of family law disputes in England and Wales with an international element is well documented in the development of domestic legislation, case law and family practice. However, despite changes to the legal landscape and the academic recognition of international family law as a legal subject, it is still often disregarded within the undergraduate family law curriculum or as a standalone module. This article explores the development of international family law in England and Wales and presents the findings of a national questionnaire into whether international family law is taught as part of the undergraduate curriculum. The article also explores what barriers exist to including international family law topics. To conclude, the author offers some general advice about incorporating these topics into the curriculum to ensure that students are equipped to deal with the realities of family practice in England and Wales.